Soil Organic Carbon in Godech Municipality, Western Bulgaria - Grigorov, Borislav; Assenov, Assen (European Journal of Sustainable Development, 2020)
The current study aims at examining soil organic carbon levels at the territory of Godech Municipality - one of the municipalities of Sofia Province, located in the western part of Bulgaria. The investigation includes information about some of the latest global studies, regarding soil organic carbon, including those, conducted on Bulgarian territory. Soil organic carbon plays a key role in overall carbon sequestration and it plays a key role for sustainable development. A basis of the study is the investigation of Hengl et al. (2017) who created a global soil grids at 250 m resolution. Their datasets consist of prediction data about carbon contents in g per kg at the following depths: 0 cm, 5 cm, 15 cm, 30 cm, 60 cm, 100 cm and 200 cm. This data is analyzed and developed for the purposes of the current study. Generally, soil organic carbon contents in Godech Municipality decrease from north to south, with the largest carbon pool in Berkvoska Mountain. There is an increase of carbon stocks from subsoil to topsoil, which is consistent with other results. The outcomes of the study prove to be successful and they can be applied in other investigations of this subject. Keywords: carbon sequestration, soil organic carbon, sustainability